The Nature of Students - Siti Soleha; Maspuroh; Siti Maskupah; Nisrina Syahla; Fauzi Rohmat (Penerbit Hellow Pustaka, 2025)
The nature of students is a crucial fundamental aspect in the educational context, which requires in-depth understanding so that the learning process can be carried out effectively and efficiently. This journal aims to explore various dimensions surrounding students, starting from basic understanding, psychological potential consisting of spirituality, fikriyah, and nafsiyah, to the competencies that students must have in facing challenges in the era of globalization. The concept of insan kamil is also raised as the pinnacle of student development, which includes the integration of physical, mental, spiritual and social aspects. In this research, the author emphasizes the importance of understanding the nature of students not only to design relevant curricula, but also to create an inclusive learning environment and support the holistic development of individuals. It is hoped that, through a comprehensive approach, students can develop into individuals who excel academically and are able to contribute positively to society. This journal aims to provide broader insight to educators and other stakeholders in formulating educational strategies that are more effective and responsive to students' needs.